Eficacia de la DBT en ideación suicida en adultos jóvenes con TLP DBT. - Coello Alvarado, Kelvin Paúl (My University, 2025)
Borderline Personality Disorder (BPD) is a highly prevalent condition among young adults, marked by emotional instability, impulsivity, and persistent suicidal ideation. This paper presents an integrative review of the effectiveness of Dialectical Behavior Therapy (DBT) in reducing suicidal ideation in individuals aged 18 to 25 with BPD. A systematic theoretical review of literature published between 2015 and 2025 was conducted, prioritizing meta-analyses, randomized controlled trials, and systematic reviews. Findings suggest that DBT achieves sustained reductions in suicidal ideation through mechanisms such as emotion regulation, distress tolerance, and interpersonal effectiveness. Young adulthood represents a critical window for intervention due to neuroplasticity and prefrontal cortex development. It is concluded that DBT, when developmentally adapted, stands as the most empirically supported intervention for reducing suicidal ideation in this vulnerable population.
El Trastorno Límite de la Personalidad (TLP) en adultos jóvenes se asocia frecuentemente con ideación suicida persistente y elevada comorbilidad clínica. Este artículo presenta una revisión integrativa basada exclusivamente en estudios empíricos publicados entre 2015 y 2025, incluyendo ensayos clínicos aleatorizados, estudios controlados y revisiones sistemáticas. El objetivo fue analizar la eficacia de la Terapia Dialéctica Conductual (DBT) en la reducción de la ideación suicida en jóvenes de 18 a 25 años diagnosticados con TLP. Se identificaron mejoras sostenidas en la ideación suicida y las conductas autolesivas en los grupos tratados con DBT, particularmente cuando se implementaron protocolos completos con entrenamiento en habilidades. Los principales mecanismos de cambio fueron la regulación emocional, la tolerancia al malestar y la validación interpersonal. Los hallazgos respaldan la implementación de DBT adaptada al desarrollo juvenil como intervención prioritaria en contextos clínicos.
Keywords: TERAPIA DIALÉCTICA CONDUCTUAL; TLP; IDEACIÓN SUICIDA; JÓVENES